2016
DOI: 10.1002/chem.201603802
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II), Cobalt(II), Nickel(II), and Zinc(II) Silylene Complexes: Reaction of the Silylene [iPrNC(NiPr2)NiPr]2Si with FeBr2, CoBr2, NiBr2⋅MeOCH2CH2OMe, ZnCl2, and ZnBr2

Abstract: Reaction of the donor-stabilized silylene [iPrNC(NiPr )NiPr] Si (1) with FeBr , CoBr , NiBr ⋅MeOCH CH OMe, ZnCl , and ZnBr afforded the respective transition-metal silylene complexes 4-8, the formation of which can be described in terms of a Lewis acid/base reaction (4, 5, 7, 8) or a nucleophilic substitution reaction (6). However, the reactivity profile of silylene 1 is not only based on its strong Lewis base character; the different coordination modes of the two guanidinato ligands (4-6 vs. 7 and 8) add an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…However, in recent years, attention has shifted to silicon compounds, where the formal oxidation state of silicon is +2, popularly known as silylenes . Examples of carbonyl-free silylene complexes of 3d transition metals in the formal oxidation state +2 are now too frequent to be comprehensively listed, thanks to extensive investigations by the groups of H. Roesky, P. Roesky, Stalke, Driess, Tacke, Inoue, Khan, and many others. The coverage of the s and p blocks is also expanding and is supplemented by examples of bonding to s-/p-block Lewis acids such as boron, aluminum, calcium, germanium, tin, and lead . However, when it comes to indium, there has only been one reaction reported between a Si­(II) compound and an indium derivative.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, attention has shifted to silicon compounds, where the formal oxidation state of silicon is +2, popularly known as silylenes . Examples of carbonyl-free silylene complexes of 3d transition metals in the formal oxidation state +2 are now too frequent to be comprehensively listed, thanks to extensive investigations by the groups of H. Roesky, P. Roesky, Stalke, Driess, Tacke, Inoue, Khan, and many others. The coverage of the s and p blocks is also expanding and is supplemented by examples of bonding to s-/p-block Lewis acids such as boron, aluminum, calcium, germanium, tin, and lead . However, when it comes to indium, there has only been one reaction reported between a Si­(II) compound and an indium derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Silylenes are known for their ability to bind to, among others, low-valent transition metal complexes. 6,20,28,41,[50][51][52][53][54][55][56] For this purpose, compound 1 was treated with group 9 dimers [RhCl Compound 6 crystallizes in the monoclinic space group P2 1 / n with one molecule in the asymmetric unit (Fig. 6).…”
Section: Silylene Coordinationmentioning
confidence: 99%
“…The group of P. Roesky reported the first silylene‐zinc complexes, [ZnCl( η 2 ‐C 5 Me 5 ){Si(PhC(N t Bu) 2 )(C 5 Me 5 )}], [Zn 2 ( μ‐ Cl) 2 Ph 2 {Si(PhC(N t Bu) 2 )Ph} 2 ] and [ZnCl 2 {Si(PhC(N t Bu) 2 )Et} 2 ] (Chart 1), using PhC(N t Bu) 2 SiCl . Subsequently, the same group as well as the group of Tacke reported few more examples of silylene‐zinc complexes using PhC(N t Bu) 2 Si( η 5 ‐C 5 Me 5 ) and [ i PrNC(N i Pr 2 )N i Pr] 2 Si as ligands. In our part, we have showed that amido silylene, [PhC(N t Bu) 2 SiN(SiMe 3 ) 2 ] forms both monomeric [PhC(N t Bu) 2 Si{N(SiMe 3 ) 2 }→ZnI 2 ]⋅THF and dimeric [{PhC(N t Bu) 2 }(N(SiMe 3 ) 2 )SiZnI( μ ‐I)] 2 adducts upon reaction with ZnI 2 and these adducts are interconvertible simply by changing the solvents …”
Section: Introductionmentioning
confidence: 99%